Ukrainian medium sized business in terms of global competitive environment: national specifics, tendencies and main problems of development - Tulku, Y.I.; Kapturenko, N.G. (Економічний вісник Донбасу, 2010)
The article examines the essence and main characteristics of Ukrainian medium-sized business. The authors analyses the role SMEs sector, especially the middle sector in the economic development. The article also estimates the condition of medium business, main tendencies of development and perspectives. The author summarizes essential factors that influence on mediumsized business development. Key words: medium-sized business, economic development, business classification, productivity. У статті досліджено сутність та основні особливості українського середнього бізнесу. Проаналізовано роль сектору МСБ, особливо середніх підприємств, в економічному розвитку країни. Також в статті запропонована оцінка стану розвитку середнього підприємництва, досліджено основні тенденції та перспективи розвитку, визначені фактори, які впливають на розвиток цього сектору у вітчизняній економіці. Ключові слова: середній бізнес, економічний розвиток, класифікація бізнесу, продуктивність. В статье исследованы сущность и основные особенности украинского среднего бизнеса. Проанализирована роль сектора МСБ, выделяя при этом средний бизнес, в экономическом развитии страны. Также в статье дана оценка состояния, основных тенденций и перспектив развития среднего бизнеса; определены факторы, влияющие на его развитие в отечественной экономике. Ключевые слова: средний бизнес, экономическое развитие, классификация бизнеса, продуктивность.